The Reality of Strategic Planning in Sudanese Universities from the Viewpoint of Teaching Staff Members: A Comparison Study between Public and Private Universities, Gezira State, Sudan, 2020 - Masaad, Osman Tag Elsir (The journal of contemporary issues in business and government, 2021)
The chief objective of this study was to identify the reality of strategic planning in Sudanese universities by focusing on public and private universities in Gezira state. The study was based on primary data collected using a questionnaire distributed to 117 teaching staff members, 27 of them from Wad MedaniAhlia University, and a random sample of 90 teaching staff members was selected from the University of Gezira. The descriptive-analytical method was established by using the method of frequency and percentages for variables of a qualitative nature, and an independent sample T-test was performed to examine the difference between the public and private universities in terms of strategic planning. Also,a one-way analysis of variance was applied to test the differences in the level of teaching staff members' participation in strategic planning according to university type and employment category. The study found that the level of strategic planning practice in public universities is higher than in private universities. According to the most significant finding, the study recommended that private Sudanese universities should pay more attention to strategic planning and also should give more room for teaching staff members to participate in strategic planning processes.